Navigating personal space: investigating the relationship between risk and signalling in baboon approach behaviour - Muschinski, J (2024)
Entering physical proximity to a conspecific is a resource; it can give an individual opportunities for social learning or affiliative interactions and could provide safety from threats through association. How individuals access this space and the interactions that follow are important aspects of primate signalling and social behaviour. Within the primate signalling literature, there has been much discussion of how species-level signalling repertoires and their complexity may be affected by social complexity and risk (e.g., despotic versus egalitarian species). However, research on how signalling in individual interactions may be affected by similar factors, for example the interpersonal risk posed by an interaction to a signaller, remains limited. This thesis re-examines approach behaviour in baboons, first taking a species-level approach investigating male-male stereotyped greetings in chacma baboons (Papio ursinus griseipes) in the larger context of Papio, then examining the content, outcome, and structure of baboon approach interactions more generally across sex combinations in olive baboons (Papio anubis) and chacma baboons.